Uwarunkowania rozwoju przetwórstwa rolno-spożywczego w opinii mieszkańców Nadnidziańskiego Parku Krajobrazowego - Popławski, Łukasz (Conditionings of Development of Food-Processing in the Opinion of Nadnidziański Landscape Park's Inhabitants, 2006)
There are 72 municipalities in Świętokrzyskie Voivodeship in which 49 protected areas cover more than half of their land. These areas are usually landscape parks and protected landscape areas. Onе of those protected areas is the Nadnidziański Landscape Park. The research was conducted among inhabitants who expressed their opinions in questionnaires. This paper presents barriers and opportunities development of food processing in the opinion of Nadnidziański Landscape Park's inhabitants in the aspect of eco-development. The research was based on inhabitants' opinions concerning particular courses of development, i.e. food processing. As the main barriers for development of food processing in municipalities of the Nadnidziański Landscape Park they mentioned: the lack of financial resources for such a development, the lack of investors interested in processing development and of lack of market for products of processing. They saw, however, the opportunities for development in free legal and economic consultancy services, credit guarantee and means of transport tax allowances and exemptions.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 2, s. 248-253